2015
DOI: 10.1186/s13046-015-0197-7
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA MEG3 functions as a competing endogenous RNA to regulate gastric cancer progression

Abstract: BackgroundLong noncoding RNAs (lncRNAs) have recently emerged as important regulators in governing fundamental biological processes, and many of which are likely to have functional roles in tumorigenesis. Maternally expressed gene 3 (MEG3) gene encodes a lncRNA whose expression is lost in an expanding list of primary human tumors and tumor cell lines, however its biological role and regulatory mechanism in gastric cancer (GC) development and progression are poorly defined.MethodsQuantitative RT-PCR analysis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
215
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(224 citation statements)
references
References 34 publications
8
215
1
Order By: Relevance
“…Luo et al claimed that MEG3 can inhibit the proliferation of cancer prostate cells and induce its apoptosis (15). Peng et al maintained that the ectopic expression of MEG3 inhibits proliferation, migration and invasion, and promotes cell apoptosis in gastric cancer (16). These studies show that MEG3 has played a role in the regulation of the proliferation, apoptosis, migration and invasion of cancer cells.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Luo et al claimed that MEG3 can inhibit the proliferation of cancer prostate cells and induce its apoptosis (15). Peng et al maintained that the ectopic expression of MEG3 inhibits proliferation, migration and invasion, and promotes cell apoptosis in gastric cancer (16). These studies show that MEG3 has played a role in the regulation of the proliferation, apoptosis, migration and invasion of cancer cells.…”
Section: Discussionmentioning
confidence: 97%
“…MEG3 is expressed in many human normal tissues, but has failed to express in a variety of human tumour cells, such as non-small cell lung cancer, bladder cancer, prostate cancer and other cancers (9)(10)(11)(12)(13)(14). Additionally, many studies have articulated that MEG3 gene plays an inhibiting role in various tumour cells (15)(16)(17)(18)(19)(20). However, the functional mechanism of MEG3 in MG63 has yet to be proven.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA and mRNA co-expression network was built by significantly differently expressed lncRNA and mRNA (36). In addition, some studies also described interactions between lncRNAs and miRNAs (37)(38)(39) or lncRNAs and mRNAs (40) in GC, the results of which showed that lncRNAs may function as a part of GC related regulation network, but lncRNA functions are still poorly explored.…”
Section: Discussionmentioning
confidence: 99%
“…MEG3 is decreased in gastric cancer patients and cell lines and downregulation correlates with metastatic disease. Ectopic expression of MEG3 inhibits cell proliferation and migration and promotes apoptosis in several gastric cancer cell lines probably due to sequestration of oncogenic miR-181 (137). Another functional aspect of MEG3 was revealed in several types of cancer cell lines as its capacity to negatively regulate EMT-promoting TGFβ pathway genes (138).…”
Section: Metastasis-related Lncrnas: Category IImentioning
confidence: 99%
“…In CRC cells, GAPLINC promotes cell proliferation and invasion in vitro by binding to PTBassociated splicing factor (PSF) and non-POU-domaincontaining octamer binding protein (NONO), factors which are involved in up-regulation of EMT-promoting factor SNAI-2 (136). For maternally expressed gene 3 (MEG3) lncRNA, sponge-related and RNA-DNA triplex formation based MOA has been described (137,138). MEG3 is decreased in gastric cancer patients and cell lines and downregulation correlates with metastatic disease.…”
Section: Metastasis-related Lncrnas: Category IImentioning
confidence: 99%